A Rare Association of Celiac Disease with Turner Syndrome - Ramar, Praveen; Roy, Shuvendu (Journal of Nepal Paediatric Society, 2013)
Celiac Disease is an immune mediated enteropathy, with wide spectrum of extra intestinal manifestation and rare autoimmune and syndromic associations. We report one such exclusive extra intestinal manifestation of celiac disease with association of Turner syndrome. DOI: http://dx.doi.org/10.3126/jnps.v33i3.7829 J. Nepal Paediatr. Soc. 2013;33(3):218-219